Mask Ventilation During Induction of General Anesthesia: Influences of Obstructive Sleep Apnea. Issue 4 (August 2017) - Sato, S.; Hasegawa, M.; Okuyama, M.; Okazaki, J.; Kitamura, Y.; Sato, Y.; Ishikawa, T.; Sato, Y.; Isono, S.
Abstract : (Abstracted from Anesthesiology, 126(1):28–38, 2017) The main objective of this study was to outline and further define the mechanisms involved in difficult mask ventilation (MV), especially in those with sleep-disordered breathing (SDB). The authors hope these goals will lead to the development of new MV techniques for safe airway management during the induction of general anesthesia.